On the transmit power and delivery delay tradeoff in buffer-aided two-way relay networks - Xiaolong Lan; Qingchun Chen; Xiaohu Tang (2016 IEEE/CIC International Conference on Communications in China (ICCC), 2016)
In this paper, we study the buffer-aided collaborative relaying protocol for the two-way relay network comprising of two users and one half-duplex decode-and-forward (DF) relay. It is assumed that two users exchange information with the assistance of relay through two phases of relay receiving and relay transmitting. The adaptive transmission mode selection and power allocation problem subject to the given arrival rate constraints is formulated and analyzed by using the Lyapunov optimization framework. Our analysis in this paper discloses that there exists an inherent tradeoff between the average delivery delay and the average power consumption. More specifically, if longer delay can be tolerated, the requested information delivery rate can be realized with less power consumption.